Navigating Ethnic Identity in Neighbourhoods of Difference: Resident Perceptions in Urumqi, China - Weiler, Leah (Université d'Ottawa / University of Ottawa, 2015)
Critical urban studies has shifted in recent years toward a focus on inequality and identity-based tension in developing countries. These theories have evolved alongside pressure for inclusive urban governance that recognizes a right to difference for minorities in cities. In the rapidly urbanizing People's Republic of China, these complex issues threaten the inclusiveness of future development. Ürümqi, the capital city of Xinjiang Uyghur Autonomous Region (XUAR), has been the site of social unrest between the Han Chinese majority and the Uyghur minority for more than a century. Economic growth and urbanization have resulted in increasing inequality and tensions between Han and Uyghur people that periodically erupt in violence, as did in Ürümqi in July of 2009. These tensions are complicated by the socio-economic marginalization of minorities, and the exclusion of the overall population from urban governance processes. Following the July 2009 riots, the Xinjiang government expressed willingness for more inclusive urban development; however the local government lacks the necessary tools to facilitate participation, and as such resident perceptions go unheard. This study adapts critical urban theory and Chinese political thought for the non-democratic context of Ürümqi, China. The perceptions of local residents are evaluated using a questionnaire and focus groups, through which it is shown that resident perceptions and use of urban space are heavily affected by ethnic identity. This, coupled with the banning of Uyghur cultural practices and exclusion of residents from public affairs, exacerbates urban inequalities and identity-based tension. It is important that critical urban studies take residents' inability to participate in urban governance processes (particularly in non-democratic contexts) into account when studying the link between identity and urban space.
Keywords: China; Xinjiang; Ethnic identity; Urban space; Urban development; Identity politics